How did refugees and migrants’ solidarity initiatives become an intervention for disaster and humanitarian response during the COVID-19 pandemic in Cape Town, South Africa? - Sebakwiye, Celse; Bidandi, Fred (Frontiers in Political Science, 2024)
The impact of COVID-19 on refugees and migrants in South Africa has been profound and multifaceted. Refugees, that is, people who are vulnerable due to displacement, have faced a series of challenges exacerbated by the pandemic. These challenges include health risks, limited healthcare access, economic hardships, food insecurity, disruptions in education, mental health concerns, stigmatization, and xenophobia. The pandemic disrupted asylum procedures and hindered the delivery of humanitarian assistance. While there were efforts to address these issues, the highlighting the need for targeted support and policies to protect and assist this vulnerable population during and after the pandemic. Refugees and migrant communities are among the most vulnerable groups during disasters and humanitarian responses. This vulnerability could be exacerbated by their presence in foreign lands, where they are legitimately discriminated against due to illegality, unrecognized documents/permits, or simply being foreign. Additionally, when new arrivals or immigrant groups are perceived as poorly integrated or as rivaling locals for limited resources, declining public support might occasionally limit the scope for robust humanitarian protection measures. To minimize the economic impact of the COVID-19 pandemic, the South African government implemented a financial stimulus package that supported complimentary monitoring measures for the citizens. However, the government’s response to refugees and migrants focused mainly on closing the land border, with limited social protection for refugees and asylum seekers. Perhaps the most significant benefit of COVID-19 was global solidarity to curb its spread and humanitarian assistance in the areas of health, finance, and other relief items such as food. One can assume that the collective self of the global community exhibited high levels of solidarity despite some discrimination being observed in the areas of vaccines. Indeed, disaster-stricken communities need solidarity, not charity, as observed during the pandemic. This article theorizes how the existing structure of solidarity scholarship purposefully incorporates both the necessity of tangible responses to people’s needs and the alternative conceptions of participation and self-organization. This study utilized a qualitative approach, collecting data from selected migrant and refugee communities in urban centers of Cape Town, including participants from Bellville central business district (CBD), Parow Centre, Goodwood Centre, and Cape Town CBD, who provided humanitarian support during the pandemic. In total, seven interviews were carried out, and participants were selected depending on their availability using a combination of purposive and snowball sampling techniques. Data were analyzed thematically based on the research question. The study drew on the pragmatic realities of refugees and migrants’ solidarity initiatives and explored how they contributed to the COVID-19 humanitarian response in Cape Town, South Africa. This research aimed to investigate how solidarity initiatives led by refugees and migrants have functioned as interventions for disaster and humanitarian response in the context of the COVID-19 pandemic in Cape Town, South Africa. The study findings from participants revealed that members of refugee and migrant communities relied on a vital solidarity initiative as coping strategy in order to deal with the negative effects of the COVID-19 pandemic and quarantine restrictions.